Formation of titanium oxide thin films by reactive magnetron sputtering - N. Villa; D. A. Golosov; T. D. Nguyen (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article presents the results of studies of the dielectric characteristics of titanium oxide films deposited by reactive magnetron sputtering of a Ti target in an Ar/O2 gas mixture. Dependencies of dielectric constant, dielectric loss tangent, band gap, leakage current density on oxygen content in Ar/O2 gas mixture during film deposition were established. Films with a dielectric constant of 20-30 units, a dielectric loss tangent of 0,02, a band gap of 3,82 eV, a leakage current density of less than 1,0 A/cm2 at an electric field strength of 2,0*106 V/cm, were obtained.